2020
DOI: 10.3390/jcm9082600
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Glucose Cotransporter-2 Inhibitors at Discharge from Cardiology Hospitalization Department: Decoding A New Clinical Scenario

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT-2 inhibitors) are new glucose-lowering drugs (GLDs) with demonstrated cardiovascular benefits in patients with heart disease and type-2 diabetes mellitus (T2DM). However, their safety and efficacy when prescribed at hospital discharge are unexplored. This prospective, observational, longitudinal cohort study included 104 consecutive T2DM patients discharged from the cardiology department between April 2018 and February 2019. Patients were classified based on SGLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The percentages of patients with HF rehospitalization or cardiovascular death within 90 days were 22.1% in the control group and 11.1% in the empagliflozin group [ 28 ]. More recently, a cohort study of 104 consecutive patients discharged for acute heart failure and stratified by SGLT-2 inhibitors prescription concluded that these agents were safe, well tolerated, and associated with a reduction in all-cause and cardiovascular deaths [ 29 ]. The comparative effectiveness of cardiovascular outcomes in new users of SGLT2 inhibitors (CVD-REAL) 2 study [ 30 ], which examined cardiovascular outcomes in a large international cohort with 2,581,980 patients with diabetes and initiated SGLT2 inhibitors versus other glucose-lowering drugs, observed over 441,357 person-years of follow-up, 2646 events of HF hospitalization in the SGLT2 inhibitors group and 3,351 in control group (HR: 0.64; 95% CI: 0.50 to 0.82; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of patients with HF rehospitalization or cardiovascular death within 90 days were 22.1% in the control group and 11.1% in the empagliflozin group [ 28 ]. More recently, a cohort study of 104 consecutive patients discharged for acute heart failure and stratified by SGLT-2 inhibitors prescription concluded that these agents were safe, well tolerated, and associated with a reduction in all-cause and cardiovascular deaths [ 29 ]. The comparative effectiveness of cardiovascular outcomes in new users of SGLT2 inhibitors (CVD-REAL) 2 study [ 30 ], which examined cardiovascular outcomes in a large international cohort with 2,581,980 patients with diabetes and initiated SGLT2 inhibitors versus other glucose-lowering drugs, observed over 441,357 person-years of follow-up, 2646 events of HF hospitalization in the SGLT2 inhibitors group and 3,351 in control group (HR: 0.64; 95% CI: 0.50 to 0.82; p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, patients admitted to the hospital with acute HF decompensation will not need to stop SGLT2i medication [88], except if presenting with eGFR < 20 ml/min/1.73m 2 , cardiogenic shock or diabetic ketoacidosis. If the patient was not on SGLT2is, this treatment can be initiated after stabilization and predischarge [89]; or in the first post-discharge visit barring any contraindications or hypersensitivity.…”
Section: Sglt2is In Acute Heart Failure Settingsmentioning
confidence: 99%